Dukungan Sosial Rekan Kerja pada Mahasiswa yang Kuliah Sambil Bekerja: Studi Kasus Pada 3 Mahasiswa FISIP Universitas Jember - Mahfudz Sidiq; Hayatun Nufus (Rumah Jurnal, University of Jember, 2025)
This study explores social support strategies provided by colleagues to students of the Faculty of Social and Political Sciences, University of Jember, who work while studying. Student-workers face challenges such as academic pressure, limited time, fatigue, and role conflict. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation. The findings show that colleagues offer various forms of support, including emotional, instrumental, informational, appraisal, and network support. These strategies help student-workers manage dual-role burdens and maintain balance between academic and work responsibilities.